Elnökválasztás Horvátországban : a változás győzelme - Lőrinczné Bencze, Edit (Közép-Európai Közlemények, 2015)
The President of Croatia is elected to a five-year term by a direct vote of all citizens, with a majority vote required to win. Since Croatia’s independence the country has got three elected presidents. The first presidential election was held on 2 August 1992 and resulted in victory for Franjo Tuđman of the HDZ, who received 57.8 percent of the vote in the first round of the election. Tuđman introduced a semi-presidential system and won the second term in 1997. The next two presidential elections took place in 2000 and in 2005 and Stjepan Mesić, the candidate of the Croatian People’s Party won the office. In 2010 Ivo Josipović became the 3rd President of Croatia, becoming the first social democratic president since the independence of the country. On 11th January 2015, in the second round Croatians people elected Kolinda Grabar-Kitarović a member of the center-right Croatian Democratic Union (HDZ) as the new President of the Republic of Croatia. Her main opponent in the runoff was the outgoing president Ivo Josipović nominated by the center-left Social Democratic Party (SDP) and supported by the government's parties. This election gathers a lot of records: for the first time a woman has been elected President, for the first time the outgoing President is not confirmed for a second mandate and Grabar-Kitarović is the first HDZ 's President after Tuđman. In addition the presidential election regarded as the foreplay to the more pressing and important upcoming November parliamentary election and there could be lots of changes at political level.